Cycloaddition Reactions of Ni(0) Difluorocarbene Complexes: Investigating the Formation of Various Perfluorometallacycles - Rochon, Alexandra (Université d'Ottawa / University of Ottawa, 2019)
Formation of carbon–fluorine and carbon–fluoroalkyl bonds via transition metal complexes represents an efficient synthetic route towards a wide array of valuable fluorinated organic compounds and fluorinated metallacycles offer a potentially green and atom economical pathway towards these functionalized fluorocarbons. This thesis is focused on cycloaddition reactions of Ni=CF2 complexes with fluoroalkenes (FAs) and acetylenes. Cycloaddition reactions of the FAs vinylidene fluoride (CF2=CH2) and perfluoro(methyl vinyl ether) [CF2=CF(OCF3)] with the electron-rich Ni(0) fluorocarbene, Ni=CF2[P(OMe)3](dppe) affords stable metallacyclobutane complexes, likely through a 1,4-diradical mechanism previously investigated for analogous reactions using computational chemistry. With CF2=CHF (TrFE), however, the observed products are the C3 alkene E-CHF=CF(CF3) and the metallacyclopentane complex, Ni(C4H2F6)(dppe), derived from oxidative coupling of two additional equivalents of TrFE. It is proposed that the instability of the initially formed metallacyclobutane gives rise to a 2,1-F shift, yielding the C3 alkene complex. Reaction of the latter with excess TrFE then liberates the C3 alkene, forming the TrFE alkene complex followed by the observed metallacyclopentane product. In the reaction of 1a with chlorotrifluoroethylene (CF2=CFCl) a single regioisomer of the metallacyclobutane is observed, but reacts further in THF solvent via α-Cl migration to Ni, affording the tetrafluoroallyl complex, NiCl(CF2CF=CFH), in which one F has been replaced by a hydrogen. Finally, reaction of 1a with hexafluoropropene [CF2=CF(CF3), HFP] takes an unprecedented turn, affording the Ni trifluoromethyl perfluoroalkenyl complex from formal transfer of one F from HFP to the Ni=CF2 moiety. The capability of 1a to perform cycloaddition with a broader substrate scope was investigating by reacting it with terminal aryl-acetylenes of varying electronic parameters. Reaction of 1a with 1.5 equivalents of 4-R-phenylacetylene afforded the expected difluorometallacyclobutenes (R = H, Cl, tBu). Further observation revealed a second acetylene insertion to yield a nickelacyclohexadiene in the first example of a 4- to 6-membered ring expansion of perfluorometallacycles. The six-membered metallacycle then undergoes reductive elimination to furnish a difluorocyclopentadiene. The electronic parameters of the aryl-acetylene substrate play a dramatic role in the selectivity of product formation. The more electron-donating substrates 4-tert-butylphenylacetylene and 1-hexyne stabilize the metallacyclobutene, while the electron-withdrawing 4-chlorophenylacetylene affords a more reactive metallacyclobutene making it more prone to the second acetylene insertion. Phenylacetylene represented a middle-ground between the two systems and proved effective for further characterization studies. The electronic effect of the surrounding ancillary ligand system was also studied by substituting dppe in 1a for P(OMe)3 and dipe to give analogous Ni(0) difluorocarbene complexes 1b and 1c (dipe = 1,2-bis(diisobutylphosphino)ethane). The -acidic phosphite ligands in 1b gave exclusively nickelacyclohexadiene and difluorinated cyclopentadiene due to a reactive metallacyclobutene, whereas the more electron rich 1c formed the metallacyclobutene product almost exclusively. The results presented here will allow for future investigations of fluorinated metallacycle reactivity, increasing our ability to prepare value-added fluorocarbon products for pharma, agrochemicals, and polymer applications.
Keywords: Cycloaddition reactions; Carbon-fluoroalkyl; Carbon-fluorine